Determining Factors of Deposit Level of Islamic Bank in Indonesia - Sofyan Baehaqie; Idqan Fahmi; Irfan Syauqi Beik (Al-Iqtishad: Jurnal Ilmu Ekonomi Syariah, 2017)
One Way to maintain the stability of banking industry is by applying the deposit insurance scheme. The application of the deposit insurance scheme has an impact by increasing the level of bank deposits. The objectives of the research are to identify the factors affecting the level of deposits of Islamic banks in Indonesia and managerial implications regarding to the functions of Indonesia Deposit Insurance Corporation (LPS). The technique used is the panel data regression with fixed effect model using the data from the 11 Islamic banks for the period of 2011 -2015. The results show that the factors affecting the level of deposits of the Islamic banks in Indonesia significantly and positively include the size of banks and their non-performing financing (NPF); however, they influence the capital negatively. Based on these results, LPS is required to build or sharpen the surveillance systems as part of its early detection by doing the mapping based on the size and to monitor the bank capital structure and bank finance portfolio structure.DOI: 10.15408/aiq.v9i2.5156